Phenotyping cassava for adaptation to drought - Okogbenin, Emmanuel; Setter, Tim L.; Ferguson M; Mutegi R; Alves, A.C.; Ceballos, H.; Fregene, Martin A. (CGIAR Generation Challenge Programme, 2011)
Cassava (manioc, yuca, or mandioca; Manihot esculenta Crantz, Euphorbiaceae) is an important cash crop and food crop of resource-limited farmers in Africa, Asia, and Latin America and the Caribbean. The storage roots are utilised either fresh, as in the case of sweet cultivars low in cyanogenic glycosides, or after processing into dry products such as fl our, starch and animal feed in the case of bitter cultivars high in cyanogenic glycosides (Balagopalan, 2002; Dufour,1988; Essers, 1995; Westby, 2002). Because of its relative high productivity under conditions of erratic rainfall and low-fertility soils, 250 million Africans depend on cassava as food, with more than 90 percent of the 117 million tons produced in sub-Saharan Africa (SSA) in 2007 being used for fresh consumption and processed food (Philips et al, 2006). A study by the International Food Policy Research Institute (IFPRI) predicts an overall 2.44 percent annual growth in the use of cassava as food in SSA, closely mirroring population growth, and a growth of 1.53 percent per annum in cassava for feed (Scott et al, 2000).